Sun Exposure on the Incidence of Allergies in Adult Women - Fenti Dewi Pertiwi; Evy Damayanthi; Rimbawan Rimbawan (Jurnal Kesehatan Masyarakat, 2025)
Exposure to UVB rays in humans largely affects vitamin D synthesis, and approximately 90%–95% of vitamin D is produced in the skin. Allergic diseases have a significant impact on the health of the affected individuals. This study aimed to determine the relationship between sun exposure and the incidence of allergies in adult women. This research used a quantitative cross-sectional design. This research was conducted in Bogor from August to November 2023. The population investigated consisted of the entire adult female population living in the city of Bogor. This study used simple random sampling to select representative respondents. The data were collected using a questionnaire. The study sample comprised of 395 people. The inclusion criteria were women aged between 19 and 49 years who permanently resided in Bogor City. The exclusion criteria are women who are pregnant, breastfeeding, experiencing menopause, using hormonal contraception, and diagnosed with diabetes or other infectious or non-communicable diseases. Bivariate data was analyzed using the chi-square test to determine the relationship between sun exposure and the incidence of allergies in women in Bogor City. Processed shellfish foods and products are a common cause of allergies in women in Bogor. The frequency of sunbathing and the use of sunscreen have a significant effect on allergies. Sunbathing 2 times/week reduces allergies, whereas never sunbathing causes allergies. Sunscreen use increases allergies, and more research is needed to develop effective prevention strategies.